Retinopati Diabetik yang Mengancam Penglihatan - Oktaryona Trisera; Himayani, Rani; Apriliana, Ety; Yusran, M (Medula, 2024)
Diabetic retinopathy is a progressive microangiopathy characterized by retinal vascular damage and blockage. The global prevalence of diabetic retinopathy is 34.6%. Clinical manifestations in patients with diabetic retinopathy include aneurysms, vein dilation, vitreous hemorrhage, and hard exudates which can affect visual acuity. Progression of diabetic retinopathy can potentially threaten vision and even blindness even though initially there are no severe clinical manifestations. Visual-threatening diabetic retinopathy is classified into severe NPDR, PDR, and all DR with diabetic macular edema. The global prevalence of VTDR is 7.26% and according to research by Sasongko et al (2017) states that 1 in 4 DM patients has a vision-threatening DR condition (VTDR). The best management of DR is prevention in the form of early screening, education, and counseling, especially in DM patients. For patients who have been diagnosed with DR, follow-up treatment, laser, injection, or even surgery, depending on the severity.